Manajemen Risiko Perusahaan Pembiayaan Syariah di Indonesia - Mufti, Ridho; Fatwa, Nur; Sobari, Nurdin; Rini, Nova (DAS Institute, 2025)
Non-bank financial institutions, particularly Islamic financing companies, play a strategic role in supporting national economic activities. Islamic Financing Companies, either as fully-fledged companies or Sharia Business Units (UUS), face various complex risk challenges. According to data from the Financial Services Authority (OJK), the assets of Islamic financing companies increased significantly from IDR 27.85 trillion (2023) to IDR 33.67 trillion (2024), although their market share remains limited to below 6%. Amid these dynamics, the implementation of risk management becomes a critical element to ensure stability, sustainability, and compliance with Sharia principles. This study employs a descriptive qualitative approach through library research, analyzing the risks, principles, standards, stages, and strategies of risk management in Islamic financing companies, as well as their practices in the industry. The findings indicate that companies such as PT. Astra Sedaya Finance and PT. Sharia Multifinance Astra have adopted comprehensive risk management strategies, including internal risk control, risk oversight through risk management and compliance functions, and independent internal audits. This approach is integrated with anticipatory measures, such as policy updates, information technology development, human resource empowerment, and the implementation of business continuity plans. By adhering to ISO SNI 31000 standards and OJK regulations, these companies effectively identify, measure, monitor, and manage eight key risks, including strategic, operational, and compliance risks. This study emphasizes that the implementation of integrated and continuous risk management not only strengthens the companies’ competitiveness but also enhances stakeholder confidence in addressing the challenges of the dynamic Islamic financing industry.